Legenda Jaka Tarub : Eksistensi Sendang Bidadari di Kecamatan Tawangharjo - Mochamad Miftakhul Afif; Ruhaniyatun Ni’mah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Ki Ageng tarub or commonly known as Jaka Tarub is a character in his story who is married to an angel. The story tells about Jaka Tarub with the Seven Angels who were soaking in a lake, so the story is legendary to this day. In this study, the author researches Sendang Telaga Bidadari which is located in Sreman Hamlet, Pojok Village, Tawangharjo District, Grobogan Regency. The Sendang is a tourist attraction that has stopped since two years ago. The sendang is also the source of the history of the story of Ki Ageng Tarub or Jaka Tarub, which is called only oral literature, namely mere folklore. The sendang is also the property of the Surakarta Hadiningrat palace which is a descendant of Ki Ageng Tarub. Because Ki Ageng Tarub is the ancestor of the kings in Java. From here, the author tries to uncover the history of the authenticity of the story of Ki Ageng Tarub, because there are several relics of Ki Ageng Tarub which are now in the Surakarta Hadiningrat Palace Museum